India–EU engagement and international migration: Historical perspectives, future challenges, and policy imperatives - Basant Kumar Potnuru (IIMB Management Review, 2015)
In the absence of a multilateral framework and a rule based global structure for the governance of international migration of people in all its complexities, countries engage in bilateral or regional cooperation in an attempt to engage and harmonize international movements and work towards a win–win situation. The current paper examines if and how the bilateral relationship or engagement between India and the EU has historically evolved and influenced international migration flows between them, and what potential future challenges and policy options they face for a successful engagement and facilitation of movement of people.